2004
DOI: 10.1097/01.wad.0000127445.00442.a1
|View full text |Cite
|
Sign up to set email alerts
|

Disease Stage in Alzheimer Disease and Treatment Effects of Rivastigmine

Abstract: The efficacy and tolerability of the cholinesterase inhibitor rivastigmine in the treatment of Alzheimer disease (AD) have been demonstrated in several clinical trials, which included patients with a wide range of dementia severities. To investigate the association between severity of disease and treatment response, the combined data from three large randomized, placebo-controlled trials were analyzed. The pooled patient population was stratified into three cohorts showing moderately severe (Mini-Mental State … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 14 publications
(9 reference statements)
5
43
0
1
Order By: Relevance
“…Since group sizes were reduced for this analysis and lacked statistical power, caution is needed in interpreting these findings. Nevertheless, this finding is consonant with results from studies with other agents showing that the ADAS-Cog has greater sensitivity to detect cognitive decline and treatment effects in moderately severe versus milder AD [47][48][49] .…”
Section: Discussionsupporting
confidence: 65%
“…Since group sizes were reduced for this analysis and lacked statistical power, caution is needed in interpreting these findings. Nevertheless, this finding is consonant with results from studies with other agents showing that the ADAS-Cog has greater sensitivity to detect cognitive decline and treatment effects in moderately severe versus milder AD [47][48][49] .…”
Section: Discussionsupporting
confidence: 65%
“…Analyses of worsening of clinical symptoms have previously been reported by Kurz et al [23] and Raskind et al [24] examining the effects of rivastigmine, however, the analyses were restricted to single domains only. Analyzing single domains increases the risk of erroneously identifying fluctuation in test performance as treatment effect and disregarding deterioration in another domain.…”
Section: Discussionmentioning
confidence: 99%
“…The 23-item version, ADCS-ADL 23 , was used in the studies including mild to moderate AD patients. The 19-item version, ADCS-ADL 19 , which was specifically developed for moderate to severe AD patients [22] , was used in the studies including moderate to severe AD patients.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…If ChEI treatment can slow or stabilize the expected decline this could represent a clinical benefit [37] . The issue of heterogeneity of response has with few exceptions [38][39][40] not often been addressed in most of the second generation ChEI trials but was observed and discussed in the tacrine trials [41] . We could demonstrate a heterogeneity of response in this study simply by describing the MMSE and the ADAS-cog change in the three different global response groups defined by the CIBIC score.…”
Section: Discussionmentioning
confidence: 99%